Funding Strategies for Rapid Growth Businesses in South Africa at Different Stages of Development - Govender, Keith (My University, 2012)
This dissertation seeks to understand the funding strategies adopted by South African businesses to enable rapid rates of growth. The importance of business growth to the development of the South African economy, as well as job creation, is frequently cited in the literature. The ability of a business to grow rapidly and develop to a sustainable level of maturity is therefore highly attractive for all stakeholders involved. However, there does not appear to be much focus in identifying which factors, both internal and external, will enable businesses to successfully manage this growth. This research serves to uncover the key issues where this gap exists. Nine rapid growth South African businesses across different stages of development were interviewed to gain insight into the challenges faced by rapid growth businesses from a funding perspective as well as to determine the tactics and strategies employed that have enabled them to survive in a rapid growth environment. A qualitative research approach, underpinned by an interpretive research paradigm, was adopted as it was believed that the researcher could best understand the meaning that the businesses ascribed to the issue of funding rapid growth by conducting face-to-face interviews. The study has produced interesting findings on the strategic orientation of rapid growth businesses and their approach to funding. It has emerged that funding of many businesses appear to be more of a reactive process than the formulation and development of a well researched strategy. Bootstrapping, which is commonly associated with start-ups and early stage businesses, was found to be employed by some of the larger companies in this study. The rapid growth businesses also employ a variety of tactics to leverage their sources of funding or to avoid external sources of funding. The research is of particular importance within the South African context as the country has been characterised by an alarmingly high failure rate of small businesses. The implications of the findings will be useful for external stakeholders such as government, policy-makers and investors as well as for the management of current and potential rapid growth businesses who can take the necessary steps to ensure that they have geared themselves as effectively as possible for a rapid increase in growth.
MBA thesis - WBS
Keywords: Funding - South Africa; Business growth; Investment - South Africa